Kebijakan Pemerintah dalam Menetapkan Upah Minimum yang Layak di Era Revolusi Industri 4.0: KEBIJAKAN PEMERINTAH DALAM MENETAPKAN UPAH MINIMUM YANG LAYAK DI ERA REVOLUSI INDUSTRI 4.0 - Tjakradirana, Erri; Rosida, Nina; Wijaya, Endra (Mendapo: Journal of Administrative Law, 2024)
This study discusses government policies regarding minimum wage determination which are related to the conditions of the Industrial Revolution 4.0 era. Industrial Revolution 4.0 is full of the use of sophisticated information technology. So, have these conditions been taken into consideration in the minimum wage setting policy? This study uses normative legal research method with qualitative data analysis. This study concludes that so far, wage policies have not optimally considered or responded to the needs of the Industrial Revolution 4.0 era faced by workers. Potentially, the educational aspect could actually be an important factor for workers to be able to adapt in the midst of the Industrial Revolution 4.0 era. The efforts to increase the amount of calculating the education element for workers as part of the minimum wage component have become urgent to be realized.